High-strength high-temperature-resistant ABS (acrylonitrile butadiene styrene) plastic plate and preparation process thereof
Through the combination of copper-plated basalt fibers and aamlated acrylonitrile-butadiene-styrene terpolymers, the problem of ABS plastics being easily deformed at high temperatures is solved, significantly improving its heat resistance and strength, and prolonging thermal deformation Temperature improves the application range.
Patent Information
- Application Number
- CN202411631161.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional ABS plastics are prone to deform under high temperature environments, limiting their application range, and the prior art is difficult to effectively improve their heat resistance and strength.
Using copper-plated basalt fibers and aminated acrylonitrile-butadiene-styrene terpolymers, the strength and heat resistance of basalt fibers are enhanced by copper-plated and amino-aminolated treatments, and their compatibility with ABS plastics is improved. , combined with polystyrene butadiene copolymer, masbutadiene anhydride, diisopropyl peroxide and other materials, prepare high-strength high-temperature resistant ABS plastic sheets.
It significantly improves the mechanical properties and high temperature resistance of ABS plastic sheets, extends the thermal deformation temperature, and improves its stability and application range in high temperature environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic sheets, in particular to a high-strength and high-temperature-resistant ABS plastic sheet and a preparation process thereof. Background Art
[0002] ABS plastic is widely used in the fields of automobiles, electronics, home appliances, photovoltaic pads, etc. due to its excellent formability, toughness and impact resistance. Photovoltaic pads are an accessory used in photovoltaic power stations. Their main function is to fill the gap between photovoltaic cell components and brackets. Photovoltaic pads can also ensure the contact area between the components and the brackets, so that the solar components can be stably fixed on the brackets. ABS plastic is an important component of photovoltaic pads. However, traditional ABS plastics are prone to deformation in high temperature environments, which limits its application range. The development of new preparation processes can not only improve the heat resistance and strength of ABS plastic board materials, but also reduce production costs and improve production efficiency. This will promote the widespread application of high-strength and high-temperature resistant ABS plastics in photovoltaic panels and other high-demand fields.
[0003] In order to solve the above problems and improve the strength and high temperature resistance of ABS plastic sheet, the present invention provides a high-strength and high-temperature resistant ABS plastic sheet and a preparation process thereof. Summary of the invention
[0004] The object of the present invention is to provide a high-strength and high-temperature resistant ABS plastic sheet and a preparation process thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A preparation process of a high-strength and high-temperature resistant ABS plastic sheet comprises the following steps:
[0007] Step 1: Take a tris(hydroxymethyl)aminomethane solution, add hydrochloric acid to adjust the pH value to 8.2-8.5, and obtain a Tris-HCl buffer; dissolve dopamine hydrochloride in the Tris-HCl buffer to obtain a dopamine solution; take the dopamine solution, add the copper-plated basalt fiber, heat it to 65-70° C., stir it for 6-10 hours, filter, wash, and dry it to obtain a modified copper-plated basalt fiber;
[0008] Step 2: taking polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mixing them evenly, melt-extruding and pelletizing to obtain a mixture A;
[0009] Step 3: Take mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood powder, modified copper-plated basalt fiber, calcium carbonate, lubricant, and toughening agent, mix them evenly, extrude at 150-160°C, granulate, add foaming agent, stir evenly, extrude, melt, plasticize, shear, and grind to obtain high-strength and high-temperature resistant ABS plastic sheet.
[0010] More optimally, the ABS plastic sheet comprises the following ingredients, by weight: 100-105 parts of polystyrene butadiene copolymer, 3-5 parts of maleic anhydride, 0.2-0.4 parts of diisopropylbenzene peroxide, 6-10 parts of mixture A, 75-80 parts of ABS plastic, 25-30 parts of amino acrylonitrile-butadiene-styrene terpolymer, 40-60 parts of wood flour, 6-10 parts of modified copper-plated basalt fiber, 2-4 parts of calcium carbonate, 1.5-2.5 parts of lubricant, 7-10 parts of toughening agent, and 1-2 parts of foaming agent.
[0011] More optimally, the preparation method of the copper-plated basalt fiber is: adding the activated basalt fiber to a copper plating solution heated to 60-65° C., stirring for 60-90 minutes, taking out, and drying at 85-90° C. for 4-5 hours to obtain the copper-plated basalt fiber.
[0012] More optimally, the method for preparing activated basalt fiber comprises the following steps:
[0013] S1: taking basalt fiber, washing and drying it to obtain washed basalt fiber; taking concentrated nitric acid and concentrated sulfuric acid, stirring them evenly to obtain a mixed solution; taking the washed basalt fiber and the mixed solution, soaking them for 5-6 hours, washing them, and obtaining roughened basalt fiber;
[0014] S2: taking the roughened basalt fiber and stannous chloride solution, soaking for 5-10 minutes to obtain sensitized basalt fiber;
[0015] S3: taking the sensitized basalt fiber and the silver nitrate solution, soaking them for 10-15 minutes, and then washing them to obtain activated basalt fiber.
[0016] More optimally, the preparation method of the copper plating solution is: take copper sulfate, formaldehyde, disodium ethylenediaminetetraacetic acid, sodium potassium tartrate, potassium ferrocyanide, and bipyridine, stir evenly, add sodium hydroxide solution, adjust the pH value to 12.0-12.5, and obtain a copper plating solution.
[0017] More optimally, the method for preparing the amino acrylonitrile-butadiene-styrene terpolymer comprises the following steps:
[0018] Step A: The preparation method of the amino acrylonitrile-butadiene-styrene terpolymer is as follows: take acrylonitrile-butadiene-styrene terpolymer, deionized water and butanone, heat to 90-92° C. and stir evenly, drop pyridine, reflux for 1-2 hours, cool to 25-30° C., pour the obtained solution into cyclohexane for precipitation, wash and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer;
[0019] Step B: Take the treated acrylonitrile-butadiene-styrene terpolymer, octadecylamine and N,N-dimethylformamide, heat to 70-75°C and stir for 4-5 hours, pour the obtained solution into toluene for precipitation, filter, wash and dry to obtain the amino acrylonitrile-butadiene-styrene terpolymer.
[0020] More optimally, the lubricant is any one or more of polyethylene wax and zinc stearate.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention prepares a high-strength and high-temperature resistant ABS plastic sheet, adds copper-plated basalt fiber, and uses electroplating liquid to copper-plated the basalt fiber, thereby enhancing the strength of the basalt fiber and the heat resistance of the basalt fiber, and improving the mechanical properties and high-temperature resistance of the ABS plastic sheet. The copper-plated basalt fiber is further modified by coating with polydopamine, so that the surface of the copper-plated basalt fiber has amino groups.
[0023] 2. The present invention uses octadecylamine to perform amination treatment on acrylonitrile-butadiene-styrene terpolymer, thereby improving the mobility of molecular chain segments, so that the amino groups on the acrylonitrile-butadiene-styrene terpolymer can react with the amino groups on the surface of the basalt fiber, thereby improving the compatibility of the modified copper-plated basalt fiber and ABS, thereby enhancing the mechanical properties of the ABS plastic sheet. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] There are no special restrictions on the manufacturers of all raw materials involved in the present invention, and illustratively include: basalt fiber: specification: 9mm, which can be purchased from Shanghai Chenqi Chemical Technology Co., Ltd.; acrylonitrile-butadiene-styrene terpolymer: ABS, CAS: 9003-56-9, molecular formula: C45H51N3X2, which can be purchased from Nantong Runfeng Petrochemical Co., Ltd.; polystyrene butadiene copolymer: model: P886285, which can be purchased from McLean Reagent; chlorinated polyethylene: model: P909270, which can be purchased from McLean Reagent; ABS plastic: model: PA-765A; which can be purchased from Taiwan Chi Mei; wood powder: model: 0654, which can be purchased from Lingshou County Kunna Mineral Products Processing Plant.
[0026] Embodiment 1: A process for preparing a high-strength and high-temperature resistant ABS plastic sheet, comprising the following steps:
[0027] Step 1: Preparation of copper-coated basalt fiber:
[0028] S1: Take basalt fiber, wash and dry it to obtain washed basalt fiber; take concentrated nitric acid with a concentration of 68% and concentrated sulfuric acid with a concentration of 98%, stir them evenly to obtain a mixed solution; take 10g of the washed basalt fiber and 30g of the mixed solution, soak them for 5.5h, wash them, and obtain roughened basalt fiber;
[0029] S2: Take 10g of the roughened basalt fiber and 30g of a 5wt% stannous chloride solution, soak for 8min to obtain sensitized basalt fiber; take 10g of the sensitized basalt fiber and 30g of a 10wt% silver nitrate solution, soak for 12min, and then wash to obtain activated basalt fiber;
[0030] S3: Take 15 g / L of copper sulfate, 15 mL / L of formaldehyde, 25 g / L of disodium ethylenediaminetetraacetate, 20 g / L of potassium sodium tartrate, 0.02 g / L of potassium ferrocyanide, and 0.006 g / L of bipyridine, stir evenly, add sodium hydroxide solution, adjust the pH value to 12.5, and obtain a copper plating solution;
[0031] S4: adding the activated basalt fiber to a copper plating solution heated to 62° C., stirring for 80 min, taking out, and drying at 88° C. for 4.5 h to obtain a copper-plated basalt fiber;
[0032] Step 2: Preparation of modified copper-plated basalt fiber:
[0033] Take 10mmol / L tris(hydroxymethyl)aminomethane solution, add hydrochloric acid to adjust the pH value to 8.3, and obtain Tris-HCl buffer; dissolve dopamine hydrochloride in Tris-HCl buffer to obtain a dopamine solution with a concentration of 2g / L; take 200mL dopamine solution, add 4g copper-plated basalt fiber, heat to 68°C, stir for 8h, filter, wash, and dry to obtain modified copper-plated basalt fiber;
[0034] Step 3: Preparation of amination acrylonitrile-butadiene-styrene terpolymer:
[0035] S1: Take 2.5g of acrylonitrile-butadiene-styrene terpolymer, 10mL of deionized water, and 90mL of butanone, heat to 91°C and stir evenly, add 0.15mL of pyridine dropwise, reflux for 1.5h, cool to 28°C, pour the obtained solution into cyclohexane for precipitation, wash, and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer;
[0036] S2: Take 2 g of the treated acrylonitrile-butadiene-styrene terpolymer, 1.2 g of octadecylamine, and 100 mL of N,N-dimethylformamide, heat to 72° C. and stir for 4.5 h, pour the obtained solution into toluene for precipitation, filter, wash, and dry to obtain an amino acrylonitrile-butadiene-styrene terpolymer;
[0037] Step 4: Preparation of high-strength and high-temperature resistant ABS plastic sheet:
[0038] Take polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mix them evenly, melt extrude them and pelletize them to obtain mixture A;
[0039] Mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood flour, modified copper-plated basalt fiber, calcium carbonate, lubricant polyethylene wax, toughening agent chlorinated polyethylene, mix them evenly, extrude at 155°C, granulate, add foaming agent azodicarbonamide, stir evenly, extrude, melt, plasticize, shear, and grind to obtain a 4 mm thick high-strength and high-temperature resistant ABS plastic sheet;
[0040] The ABS plastic sheet comprises the following ingredients, measured by weight: 102 parts of polystyrene butadiene copolymer, 4 parts of maleic anhydride, 0.3 parts of dicumyl peroxide, 8 parts of mixture A, 78 parts of ABS plastic, 27 parts of amino acrylonitrile-butadiene-styrene terpolymer, 50 parts of wood powder, 8 parts of modified copper-plated basalt fiber, 3 parts of calcium carbonate, 2 parts of lubricant polyethylene wax, 8 parts of toughening agent chlorinated polyethylene, and 1.5 parts of foaming agent azodicarbonamide.
[0041] Embodiment 2: A process for preparing a high-strength and high-temperature resistant ABS plastic sheet, comprising the following steps:
[0042] Step 1: Preparation of copper-coated basalt fiber:
[0043] S1: Take basalt fiber, wash and dry it to obtain washed basalt fiber; take concentrated nitric acid with a concentration of 68% and concentrated sulfuric acid with a concentration of 98%, stir them evenly to obtain a mixed solution; take 10g of the washed basalt fiber and 30g of the mixed solution, soak them for 5h, wash them, and obtain roughened basalt fiber;
[0044] S2: taking 10g of the roughened basalt fiber and 30g of a 5wt% stannous chloride solution, soaking for 5min to obtain sensitized basalt fiber; taking 10g of the sensitized basalt fiber and 30g of a 10wt% silver nitrate solution, soaking for 10min, and washing to obtain activated basalt fiber;
[0045] S3: Take 15 g / L of copper sulfate, 15 mL / L of formaldehyde, 25 g / L of disodium ethylenediaminetetraacetate, 20 g / L of potassium sodium tartrate, 0.02 g / L of potassium ferrocyanide, and 0.006 g / L of bipyridine, stir evenly, add sodium hydroxide solution, adjust the pH value to 12.5, and obtain a copper plating solution;
[0046] S4: adding the activated basalt fiber to a copper plating solution heated to 60° C., stirring for 60 min, taking out, and drying at 85° C. for 4 h to obtain copper-plated basalt fiber;
[0047] Step 2: Preparation of modified copper-plated basalt fiber:
[0048] Take 10mmol / L tris(hydroxymethyl)aminomethane) solution, add hydrochloric acid to adjust the pH value to 8.2, and obtain Tris-HCl buffer; dissolve dopamine hydrochloride in Tris-HCl buffer to obtain a dopamine solution with a concentration of 2g / L; take 200mL dopamine solution, add 4g copper-plated basalt fiber, heat to 65°C, stir for 6h, filter, wash, and dry to obtain modified copper-plated basalt fiber;
[0049] Step 3: Preparation of amination acrylonitrile-butadiene-styrene terpolymer:
[0050] S1: Take 2.5g of acrylonitrile-butadiene-styrene terpolymer, 10mL of deionized water, and 90mL of butanone, heat to 90°C and stir evenly, add 0.15mL of pyridine dropwise, reflux for 1h, cool to 25°C, pour the obtained solution into cyclohexane for precipitation, wash, and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer;
[0051] S2: Take 2 g of the treated acrylonitrile-butadiene-styrene terpolymer, 1.2 g of octadecylamine, and 100 mL of N,N-dimethylformamide, heat to 70° C. and stir for 4 h, pour the obtained solution into toluene for precipitation, filter, wash, and dry to obtain an amino acrylonitrile-butadiene-styrene terpolymer;
[0052] Step 4: Preparation of high-strength and high-temperature resistant ABS plastic sheet:
[0053] Take polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mix them evenly, melt extrude them and pelletize them to obtain mixture A;
[0054] Mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood flour, modified copper-plated basalt fiber, calcium carbonate, lubricant zinc stearate, toughening agent chlorinated polyethylene, mix them evenly, extrude at 150°C, granulate, add foaming agent azodicarbonamide, stir evenly, extrude, melt, plasticize, shear, and grind to obtain a 4 mm thick high-strength and high-temperature resistant ABS plastic sheet;
[0055] The ABS plastic sheet comprises the following components, by weight: 100 parts of polystyrene butadiene copolymer, 3 parts of maleic anhydride, 0.2 parts of dicumyl peroxide, 6 parts of mixture A, 75 parts of ABS plastic, 25 parts of amino acrylonitrile-butadiene-styrene terpolymer, 40 parts of wood powder, 6 parts of modified copper-plated basalt fiber, 2 parts of calcium carbonate, 1.5 parts of lubricant zinc stearate, 7 parts of toughening agent chlorinated polyethylene, and 1 part of foaming agent azodicarbonamide.
[0056] Embodiment 3: A process for preparing a high-strength and high-temperature resistant ABS plastic sheet, comprising the following steps:
[0057] Step 1: Preparation of copper-coated basalt fiber:
[0058] S1: Take basalt fiber, wash and dry it to obtain washed basalt fiber; take concentrated nitric acid with a concentration of 68% and concentrated sulfuric acid with a concentration of 98%, stir them evenly to obtain a mixed solution; take 10g of the washed basalt fiber and 30g of the mixed solution, soak them for 6h, wash them, and obtain roughened basalt fiber;
[0059] S2: taking 10g of the roughened basalt fiber and 30g of a 5wt% stannous chloride solution, soaking for 10min to obtain sensitized basalt fiber; taking 10g of the sensitized basalt fiber and 30g of a 10wt% silver nitrate solution, soaking for 15min, and washing to obtain activated basalt fiber;
[0060] S3: Take 15 g / L of copper sulfate, 15 mL / L of formaldehyde, 25 g / L of disodium ethylenediaminetetraacetate, 20 g / L of potassium sodium tartrate, 0.02 g / L of potassium ferrocyanide, and 0.006 g / L of bipyridine, stir evenly, add sodium hydroxide solution, adjust the pH value to 12.5, and obtain a copper plating solution;
[0061] S4: adding the activated basalt fiber to a copper plating solution heated to 65° C., stirring for 90 min, taking it out, and drying it at 90° C. for 5 h to obtain a copper-plated basalt fiber;
[0062] Step 2: Preparation of modified copper-plated basalt fiber:
[0063] Take 10mmol / L tris(hydroxymethyl)aminomethane) solution, add hydrochloric acid to adjust the pH value to 8.5, and obtain Tris-HCl buffer; dissolve dopamine hydrochloride in Tris-HCl buffer to obtain a dopamine solution with a concentration of 2g / L; take 200mL dopamine solution, add 4g copper-plated basalt fiber, heat to 70℃, stir for 10h, filter, wash, and dry to obtain modified copper-plated basalt fiber;
[0064] Step 3: Preparation of amination acrylonitrile-butadiene-styrene terpolymer:
[0065] S1: Take 2.5g acrylonitrile-butadiene-styrene terpolymer, 10mL deionized water, and 90mL butanone, heat to 92°C and stir evenly, add 0.15mL pyridine dropwise, reflux for 2h, cool to 30°C, pour the obtained solution into cyclohexane for precipitation, wash, and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer;
[0066] S2: Take 2 g of the treated acrylonitrile-butadiene-styrene terpolymer, 1.2 g of octadecylamine, and 100 mL of N,N-dimethylformamide, heat to 75° C. and stir for 5 h, pour the obtained solution into toluene for precipitation, filter, wash, and dry to obtain an amino acrylonitrile-butadiene-styrene terpolymer;
[0067] Step 4: Preparation of high-strength and high-temperature resistant ABS plastic sheet:
[0068] Take polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mix them evenly, melt extrude them and pelletize them to obtain mixture A;
[0069] Mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood flour, modified copper-plated basalt fiber, calcium carbonate, lubricant polyethylene wax, toughening agent chlorinated polyethylene, mix them evenly, extrude at 150-160°C, granulate, add azodicarbonamide as a foaming agent, stir evenly, extrude, melt, plasticize, shear, and grind to obtain a 4mm thick high-strength and high-temperature resistant ABS plastic sheet;
[0070] The ABS plastic sheet comprises the following components, by weight: 105 parts of polystyrene butadiene copolymer, 5 parts of maleic anhydride, 0.4 parts of dicumyl peroxide, 10 parts of mixture A, 80 parts of ABS plastic, 30 parts of amino acrylonitrile-butadiene-styrene terpolymer, 60 parts of wood powder, 10 parts of modified copper-plated basalt fiber, 4 parts of calcium carbonate, 2.5 parts of lubricant polyethylene wax, 10 parts of toughening agent chlorinated polyethylene, and 2 parts of foaming agent azodicarbonamide.
[0071] Comparative Example 1: The basalt fiber is not subjected to copper plating, and the rest is the same as Example 1:
[0072] Step 1: Preparation of modified basalt fiber:
[0073] Take 10mmol / L tris(hydroxymethyl)aminomethane solution, add hydrochloric acid to adjust the pH value to 8.3, and obtain Tris-HCl buffer; dissolve dopamine hydrochloride in Tris-HCl buffer to obtain a dopamine solution with a concentration of 2g / L; take 200mL dopamine solution, add 4g basalt fiber, heat to 68℃, stir for 8h, filter, wash and dry to obtain modified basalt fiber;
[0074] Step 2: Preparation of amination acrylonitrile-butadiene-styrene terpolymer:
[0075] S1: Take 2.5g of acrylonitrile-butadiene-styrene terpolymer, 10mL of deionized water, and 90mL of butanone, heat to 91°C and stir evenly, add 0.15mL of pyridine dropwise, reflux for 1.5h, cool to 28°C, pour the obtained solution into cyclohexane for precipitation, wash, and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer;
[0076] S2: Take 2 g of the treated acrylonitrile-butadiene-styrene terpolymer, 1.2 g of octadecylamine, and 100 mL of N,N-dimethylformamide, heat to 72° C. and stir for 4.5 h, pour the obtained solution into toluene for precipitation, filter, wash, and dry to obtain an amino acrylonitrile-butadiene-styrene terpolymer;
[0077] Step 3: Preparation of high-strength and high-temperature resistant ABS plastic sheet:
[0078] Take polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mix them evenly, melt extrude them and pelletize them to obtain mixture A;
[0079] Mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood flour, modified basalt fiber, calcium carbonate, lubricant polyethylene wax, toughening agent chlorinated polyethylene, mix well, extrude at 155°C, granulate, add foaming agent azodicarbonamide, stir well, extrude, melt, plasticize, shear, and grind to obtain a 4 mm thick high-strength and high-temperature resistant ABS plastic sheet;
[0080] The ABS plastic sheet comprises the following ingredients, measured by weight: 102 parts of polystyrene butadiene copolymer, 4 parts of maleic anhydride, 0.3 parts of dicumyl peroxide, 8 parts of mixture A, 78 parts of ABS plastic, 27 parts of amino acrylonitrile-butadiene-styrene terpolymer, 50 parts of wood powder, 8 parts of modified basalt fiber, 3 parts of calcium carbonate, 2 parts of lubricant polyethylene wax, 8 parts of toughening agent chlorinated polyethylene, and 1.5 parts of foaming agent azodicarbonamide.
[0081] Comparative Example 2: The copper-plated basalt fiber is not modified, and the rest is the same as Example 1:
[0082] Step 1: Preparation of copper-coated basalt fiber:
[0083] S1: Take basalt fiber, wash and dry it to obtain washed basalt fiber; take concentrated nitric acid with a concentration of 68% and concentrated sulfuric acid with a concentration of 98%, stir them evenly to obtain a mixed solution; take 10g of the washed basalt fiber and 30g of the mixed solution, soak them for 5.5h, wash them, and obtain roughened basalt fiber;
[0084] S2: Take 10g of the roughened basalt fiber and 30g of a 5wt% stannous chloride solution, soak for 8min to obtain sensitized basalt fiber; take 10g of the sensitized basalt fiber and 30g of a 10wt% silver nitrate solution, soak for 12min, and then wash to obtain activated basalt fiber;
[0085] S3: Take 15 g / L of copper sulfate, 15 mL / L of formaldehyde, 25 g / L of disodium ethylenediaminetetraacetate, 20 g / L of potassium sodium tartrate, 0.02 g / L of potassium ferrocyanide, and 0.006 g / L of bipyridine, stir evenly, add sodium hydroxide solution, adjust the pH value to 12.5, and obtain a copper plating solution;
[0086] S4: adding the activated basalt fiber to a copper plating solution heated to 62° C., stirring for 80 min, taking out, and drying at 88° C. for 4.5 h to obtain a copper-plated basalt fiber;
[0087] Step 2: Preparation of amination acrylonitrile-butadiene-styrene terpolymer:
[0088] S1: Take 2.5g of acrylonitrile-butadiene-styrene terpolymer, 10mL of deionized water, and 90mL of butanone, heat to 91°C and stir evenly, add 0.15mL of pyridine dropwise, reflux for 1.5h, cool to 28°C, pour the obtained solution into cyclohexane for precipitation, wash, and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer;
[0089] S2: Take 2 g of the treated acrylonitrile-butadiene-styrene terpolymer, 1.2 g of octadecylamine, and 100 mL of N,N-dimethylformamide, heat to 72° C. and stir for 4.5 h, pour the obtained solution into toluene for precipitation, filter, wash, and dry to obtain an amino acrylonitrile-butadiene-styrene terpolymer;
[0090] Step 3: Preparation of high-strength and high-temperature resistant ABS plastic sheet:
[0091] Take polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mix them evenly, melt extrude them and pelletize them to obtain mixture A;
[0092] Mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood flour, copper-plated basalt fiber, calcium carbonate, lubricant polyethylene wax, toughening agent chlorinated polyethylene, mix them evenly, extrude at 155°C, granulate, add foaming agent azodicarbonamide, stir evenly, extrude, melt, plasticize, shear, and grind to obtain a 4 mm thick high-strength and high-temperature resistant ABS plastic sheet;
[0093] The ABS plastic sheet comprises the following ingredients, measured by weight: 102 parts of polystyrene butadiene copolymer, 4 parts of maleic anhydride, 0.3 parts of dicumyl peroxide, 8 parts of mixture A, 78 parts of ABS plastic, 27 parts of amino acrylonitrile-butadiene-styrene terpolymer, 50 parts of wood powder, 8 parts of copper-plated basalt fiber, 3 parts of calcium carbonate, 2 parts of lubricant polyethylene wax, 8 parts of toughening agent chlorinated polyethylene, and 1.5 parts of foaming agent azodicarbonamide.
[0094] Comparative Example 3: No amino acrylonitrile-butadiene-styrene terpolymer was added, and the rest was the same as Example 1:
[0095] Step 1: Preparation of copper-coated basalt fiber:
[0096] S1: Take basalt fiber, wash and dry it to obtain washed basalt fiber; take concentrated nitric acid with a concentration of 68% and concentrated sulfuric acid with a concentration of 98%, stir them evenly to obtain a mixed solution; take 10g of the washed basalt fiber and 30g of the mixed solution, soak them for 5.5h, wash them, and obtain roughened basalt fiber;
[0097] S2: Take 10g of the roughened basalt fiber and 30g of a 5wt% stannous chloride solution, soak for 8min to obtain sensitized basalt fiber; take 10g of the sensitized basalt fiber and 30g of a 10wt% silver nitrate solution, soak for 12min, and then wash to obtain activated basalt fiber;
[0098] S3: Take 15 g / L of copper sulfate, 15 mL / L of formaldehyde, 25 g / L of disodium ethylenediaminetetraacetate, 20 g / L of potassium sodium tartrate, 0.02 g / L of potassium ferrocyanide, and 0.006 g / L of bipyridine, stir evenly, add sodium hydroxide solution, adjust the pH value to 12.5, and obtain a copper plating solution;
[0099] S4: adding the activated basalt fiber to a copper plating solution heated to 62° C., stirring for 80 min, taking out, and drying at 88° C. for 4.5 h to obtain a copper-plated basalt fiber;
[0100] Step 2: Preparation of modified copper-plated basalt fiber:
[0101] Take 10mmol / L tris(hydroxymethyl)aminomethane solution, add hydrochloric acid to adjust the pH value to 8.3, and obtain Tris-HCl buffer; dissolve dopamine hydrochloride in Tris-HCl buffer to obtain a dopamine solution with a concentration of 2g / L; take 200mL dopamine solution, add 4g copper-plated basalt fiber, heat to 68°C, stir for 8h, filter, wash, and dry to obtain modified copper-plated basalt fiber;
[0102] Step 3: Preparation of high-strength and high-temperature resistant ABS plastic sheet:
[0103] Take polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mix them evenly, melt extrude them and pelletize them to obtain mixture A;
[0104] Mixture A, ABS plastic, wood flour, modified copper-plated basalt fiber, calcium carbonate, lubricant polyethylene wax, toughening agent chlorinated polyethylene, mix well, extrude at 155°C, granulate, add foaming agent azodicarbonamide, stir well, extrude, melt, plasticize, shear, and grind to obtain a 4mm thick high-strength and high-temperature resistant ABS plastic sheet;
[0105] The ABS plastic sheet comprises the following components, by weight: 102 parts of polystyrene butadiene copolymer, 4 parts of maleic anhydride, 0.3 parts of dicumyl peroxide, 8 parts of mixture A, 105 parts of ABS plastic, 50 parts of wood flour, 8 parts of modified copper-plated basalt fiber, 3 parts of calcium carbonate, 2 parts of lubricant polyethylene wax, 8 parts of toughening agent chlorinated polyethylene, and 1.5 parts of foaming agent azodicarbonamide.
[0106] experiment:
[0107] The 90 mm×10 mm×4 mm ABS plastic sheets prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests to test their tensile strength and flexural strength, and then the heat deformation temperature of the ABS plastic sheet was tested with reference to ASTM D 648 to characterize its heat resistance. The obtained data are shown in the following table:
[0108] Tensile strength / MPa Bending strength / MPa Heat deformation temperature / ℃ Example 1 62 157 86 Example 2 61 155 85 Example 3 62 158 86 Comparative Example 1 52 141 73 Comparative Example 2 57 147 79 Comparative Example 3 55 144 77
[0109] Conclusion: From the comparison of the data in the table, it can be seen that in Example 1, the basalt fiber is not copper-plated, and the mechanical properties and heat deformation temperature of the ABS plastic sheet are reduced, and the high temperature resistance is deteriorated. In Example 2, the copper-plated basalt fiber is not modified, and the compatibility of the copper-plated basalt fiber with ABS is poor, which affects the mechanical properties and high temperature resistance of the ABS plastic sheet. In Example 3, the acrylonitrile-butadiene-styrene terpolymer is not aminated with octadecylamine, and the compatibility of the modified copper-plated basalt fiber with ABS, the mechanical properties and high temperature resistance of the ABS plastic sheet are reduced. The ABS plastic sheet prepared by the present invention adds copper-plated basalt fiber, and the basalt fiber is copper-plated with electroplating liquid, which enhances the strength of the basalt fiber and the heat resistance of the basalt fiber, and improves the mechanical properties and high temperature resistance of the ABS plastic sheet. The acrylonitrile-butadiene-styrene terpolymer is aminated with octadecylamine, which improves the compatibility of the modified copper-plated basalt fiber with ABS, thereby enhancing the mechanical properties of the ABS plastic sheet.
[0110] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A preparation process of high-strength and high-temperature resistant ABS plastic sheet, characterized in that: The following steps are involved: Step 1: Take a tris(hydroxymethyl)aminomethane solution, add hydrochloric acid to adjust the pH value to 8.2-8.5, and obtain a Tris-HCl buffer; Dissolving dopamine hydrochloride in Tris-HCl buffer to obtain a dopamine solution; taking the dopamine solution, adding copper-plated basalt fiber, heating to 65-70° C., stirring for 6-10 hours, filtering, washing, and drying to obtain modified copper-plated basalt fiber; Step 2: taking polystyrene butadiene copolymer, maleic anhydride and dicumyl peroxide, mixing them evenly, melt-extruding and pelletizing to obtain a mixture A; Step 3: Take mixture A, ABS plastic, amino acrylonitrile-butadiene-styrene terpolymer, wood powder, modified copper-plated basalt fiber, calcium carbonate, lubricant, and toughening agent, mix them evenly, extrude at 150-160°C, granulate, add foaming agent, stir evenly, extrude, melt, plasticize, shear, and grind to obtain high-strength and high-temperature resistant ABS plastic sheet.
2. The process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to claim 1, characterized in that: The ABS plastic sheet comprises the following components, by weight: 100-105 parts of polystyrene butadiene copolymer, 3-5 parts of maleic anhydride, 0.2-0.4 parts of dicumyl peroxide, 6-10 parts of mixture A, 75-80 parts of ABS plastic, 25-30 parts of amino acrylonitrile-butadiene-styrene terpolymer, 40-60 parts of wood powder, 6-10 parts of modified copper-plated basalt fiber, 2-4 parts of calcium carbonate, 1.5-2.5 parts of lubricant, 7-10 parts of toughening agent, and 1-2 parts of foaming agent.
3. The process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to claim 1, characterized in that: The preparation method of the copper-plated basalt fiber is as follows: adding the activated basalt fiber to a copper plating solution heated to 60-65° C., stirring for 60-90 minutes, taking out, and drying at 85-90° C. for 4-5 hours to obtain the copper-plated basalt fiber.
4. The process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to claim 3, characterized in that: The method for preparing activated basalt fiber comprises the following steps: S1: taking basalt fiber, washing and drying it to obtain washed basalt fiber; taking concentrated nitric acid and concentrated sulfuric acid, stirring them evenly to obtain a mixed solution; taking the washed basalt fiber and the mixed solution, soaking them for 5-6 hours, washing them, and obtaining roughened basalt fiber; S2: taking the roughened basalt fiber and stannous chloride solution, soaking for 5-10 minutes to obtain sensitized basalt fiber; S3: taking the sensitized basalt fiber and the silver nitrate solution, soaking them for 10-15 minutes, and then washing them to obtain activated basalt fiber.
5. The process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to claim 3, characterized in that: The preparation method of the copper plating solution is as follows: copper sulfate, formaldehyde, disodium ethylenediaminetetraacetate, sodium potassium tartrate, potassium ferrocyanide and bipyridine are taken, stirred evenly, sodium hydroxide solution is added, and the pH value is adjusted to 12.0-12.5 to obtain the copper plating solution.
6. The process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to claim 1, characterized in that: The preparation method of the amino acrylonitrile-butadiene-styrene terpolymer comprises the following steps: Step A: The preparation method of the amino acrylonitrile-butadiene-styrene terpolymer is as follows: take acrylonitrile-butadiene-styrene terpolymer, deionized water and butanone, heat to 90-92° C. and stir evenly, drop pyridine, reflux for 1-2 hours, cool to 25-30° C., pour the obtained solution into cyclohexane for precipitation, wash and dry to obtain the treated acrylonitrile-butadiene-styrene terpolymer; Step B: Take the treated acrylonitrile-butadiene-styrene terpolymer, octadecylamine and N,N-dimethylformamide, heat to 70-75°C and stir for 4-5 hours, pour the obtained solution into toluene for precipitation, filter, wash and dry to obtain the amino acrylonitrile-butadiene-styrene terpolymer.
7. The process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to claim 2, characterized in that: The lubricant is any one or more of polyethylene wax and zinc stearate.
8. An ABS plastic sheet prepared according to the process for preparing a high-strength and high-temperature-resistant ABS plastic sheet according to any one of claims 1 to 7.
Citation Information
Patent Citations
Chopped basalt fiber reinforced ABS resin composite material and preparation method and application thereof
CN106084624A
Method for preparing oxidized-graphene-grafted basalt fiber multi-scale reinforcement body
CN107254066A
Surface palladium-free chemical copper plating method of polytetrafluoroethylene materials
CN107955939A
Method for improving interface bonding strength of fiber reinforced thermoplastic composite material
CN113583267A
Method for preparing ultrahigh-conductivity Cu / basalt fiber composite material by adopting electroless copper deposition
CN118899122A